2015
DOI: 10.1101/cshperspect.a021428
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response in Hepatitis B Virus Infection

Abstract: Hepatitis B virus (HBV) can replicate within hepatocytes without causing direct cell damage. The host immune response is, therefore, not only essential to control the spread of virus infection, but it is also responsible for the inflammatory events causing liver pathologies. In this review, we discuss how HBV deals with host immunity and how we can harness it to achieve virus control and suppress liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 160 publications
(135 reference statements)
2
109
0
Order By: Relevance
“…As discussed by Tan et al 2015, the likelihood of progression to chronicity, following infection with HBV, is predominantly determined by age at infection. Infants infected at birth develop chronic infection in 90% of cases, whereas for children aged between 1 and 5 years, this falls to 25% -30%, and, for immunocompetent adults, the likelihood of progression to chronicity is 5% (Edmunds et al 1993).…”
Section: Natural History Infection and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed by Tan et al 2015, the likelihood of progression to chronicity, following infection with HBV, is predominantly determined by age at infection. Infants infected at birth develop chronic infection in 90% of cases, whereas for children aged between 1 and 5 years, this falls to 25% -30%, and, for immunocompetent adults, the likelihood of progression to chronicity is 5% (Edmunds et al 1993).…”
Section: Natural History Infection and Immunitymentioning
confidence: 99%
“…These phases, described in more detail in Tan et al (2015), are: † immune tolerance-high infectivity, little ongoing liver damage; † immune clearance-variable infectivity, active inflammation of the liver; † immune control-low infectivity, little ongoing liver damage; and † immune escape-variable infectivity, recurrent liver inflammation.…”
Section: Natural History Infection and Immunitymentioning
confidence: 99%
“…It depends on the intensity of immune response (function f ( v )), the initial virus load (initial condition) and the growth rate of the virus in accordance with the existing view of the regulation of virus infections [1, 2, 4, 11, 29, 33, 34, 38]. We assume that the maximal intensity of the immune response is sufficiently high to overcome virus growth and spread in a low-dose infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence prey is not only consumed by predators but it can also hunt predators [2, 29, 30]. Straightforward examples are provided by HIV, HBV and HCV infections in humans [3133] and experimental LCMV infection in mice [3437]. In this paper we propose a model of spatiotemporal virus infection dynamics which considers a non-linear bell-shaped regulation of the cytotoxic T cells response with a time lag needed for their clonal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Both frequencies and magnitudes of response were significantly lower in these patients compared to HBsAg loss subjects. We also showed that both CD4 + and CD8 + T cells contributed to the anti‐HBV immune responses by secreting IFN‐γ CD4 + T cells are robust producers of cytokines and required for the efficient development of effector CD8 + CTLs . Our IFN‐γ ICS analysis revealed that especially HBV Core IFN‐γ‐secreting CD4 + subsets were significantly lower in CHB patients compared with HBsAg loss subjects.…”
Section: Discussionmentioning
confidence: 99%